The Economic Value Zone of Semarang Zoo Using Travel Cost and Contingent Valuation Method - Hana Sugiastu Firdaus; Muhammad Adnan Yusuf; Ahmad Bassam (Journal of Applied Geospatial Information, 2023)
Semarang City is one of the cities in Central Java which has a lot of potential and tourist attractions that can be developed further. The city offers diverse destinations, including Semarang Zoo. In 2007, the Municipal Government of Semarang relocated the zoo from Tinjomoyo Zoo to a new site in the Mangkang area and renamed it Semarang Zoo. Currently, Semarang Zoo is a man-made tourist attraction. The presence of these tourist areas has a substantial impact on the local economy, benefiting the surrounding communities. To assess the post-relocation development of tourist areas, an analysis of the economic value zones was conducted using the Travel Cost Method (TCM) and the Contingent Valuation Method (CVM) to determine the total economic value of the tourist areas. The Hedonic Pricing Method (HPM) was employed to gauge tourism potential based on visitor preferences. The Gravity Model was also utilized to measure the attractiveness of both tourist areas. The sample sizes for Semarang Zoo were 110 for TCM, 105 for CVM, and 110 for HPM. The research findings revealed that Semarang Zoo has a total economic value of IDR 245,895,813,400 and the highest hedonic value of 3.050. The calculated hedonic value suggests a preference value of 3, indicating an average level of preference. Based on the calculation of spatial interactions, it shows that the biggest attractions of the Semarang Zoo are Semarang City and Kendal City.